A Legal Framework for Artificial Intelligence-Assisted Halal Certification: Indonesia's Regulatory Sandbox - Yuanitasari, Deviana; Chairunnisa, Madiha Dzakiyyah; Salaeh, Yamudin (Jurnal Media Hukum, 2026)
Halal certification in Indonesia, governed by Law No. 33 of 2014 on Halal Product Assurance (UUPJPH), is essential for consumer protection and the competitiveness of micro, small, and medium enterprises (MSMEs) in the global halal market. However, the current process faces challenges of administrative inefficiency, high costs, and uneven institutional capacity, which hinder MSME compliance. This study aims to explore how Artificial Intelligence (AI) can be integrated into Indonesia’s halal certification framework to enhance efficiency, transparency, and accessibility while preserving legal and religious integrity. Using a socio-legal research method, the study combines doctrinal legal analysis of relevant laws and regulations with empirical insights from current practices and comparative experiences in Malaysia and the United Arab Emirates. The findings indicate that AI, when introduced through a regulatory sandbox under BPJPH leadership, can streamline document verification, risk assessment, and post-market surveillance without replacing human responsibility or religious authority. The study proposes a phased implementation data infrastructure first, AI-assisted tasks next, followed by risk triage and traceability supported by strong data governance, explainable models, and appeal mechanisms. This approach can deliver a halal certification system that is faster, fairer, and more credible, enabling MSMEs to thrive in an increasingly digital economy.